Social Networks of Lesbian, Gay, Bisexual, and Transgender Older Adults - Erosheva, Elena A. (Res Aging, 2015)
PURPOSE: This study examines global social networks—including friendship, support, and acquaintance networks—of lesbian, gay, bisexual, and transgender (LGBT) older adults. DESIGN AND METHODS: Utilizing data from a large community-based study, we employ multiple regression analyses to examine correlates of social network size and diversity. RESULTS: Controlling for background characteristics, network size was positively associated with being female, transgender identity, employment, higher income, having a partner or a child, identity disclosure to a neighbor, engagement in religious activities, and service use. Controlling in addition for network size, network diversity was positively associated with younger age, being female, transgender identity, identity disclosure to a friend, religious activity, and service use. IMPLICATIONS: According to social capital theory, social networks provide a vehicle for social resources that can be beneficial for successful aging and well-being. This study is a first step at understanding the correlates of social network size and diversity among LGBT older adults.